PERFIL DO PERCURSO METODOLÓGICO EVIDENCIADO NA PRODUÇÃO ACADÊMICA DISCENTE DO MESTRADO EM CIÊNCIAS SOCIAIS APLICADAS DA UNIVERSIDADE ESTADUAL DE PONTA GROSSA – PR - Sgarbieiro, Marcia (2010)
The recent research has as its general aim to draw the profile of the students production with the master’s degree programme at UEPG Applied Social Science, observing how the process of research, in this area of knowledge, has been worked. The research is qualitative, however it does not exclude the quantitative approach, mainly is expressed in the elaboration of the demonstrative charts of the master’s degree dissertations defended in the years 2001 through 2007. In the context of this approach we developed an exploratory and descriptive research, sustained initially by the bibliographical research. Following we made a documental research after searching in the files of the master’s programme, the dissertations and the reports from CAPES. We also used the internet to search the Curriculum Lattes of the master’s degree students and the guide-teachers. Finally we systematized the empirical data based on the theoretical reference that had been built.